Challenges and opportunities in the global expansion of Islamic banking - Soomro, Anam; kumar, Nikash; Zakariyah, Habeebullah; Shah, Asadullah (Society for Arts and Social Sciences (SASS), 2025)
Islamic banking has become a popular banking choice because it combines ethical financial principles with rising demand for Shariah-compliant financial products. The swift expansion of Islamic banking encounters multiple obstacles to worldwide expansion because of regulatory non-uniformity limited liquidity control and the requirement for standardized practices. This research discusses both the barriers and possibilities that Islamic banking faces during its worldwide expansion by examining main regulatory elements and risk management systems and presenting real financial industry examples. The research investigates how fiscal technology supports both problem resolution and monetary inclusion expansion.